2020
DOI: 10.4102/phcfm.v12i1.2215
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal cervical cytology amongst women infected with human immunodeficiency virus in Limpopo province, South Africa

Abstract: Background: Cervical cancer remains the major public problem worldwide and the most common gynaecological malignancy in the developing world, particularly in sub-Saharan Africa.Aim: To determine the prevalence of abnormal cervical cytology amongst women with and without human immunodeficiency virus (HIV) and examine the association between HIV and histological grading.Setting: The study was conducted in Limpopo province, which is the northernmost province of South Africa. The province has five district municip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
2
1
Order By: Relevance
“…In China, CIN 1 and CIN 2 pooled prevalence of 3.4% and 1.5% has been reported [ 42 ]. Contrary to our study, Ntuli et al [ 43 ] reported a higher proportion (19.2%) of abnormal cytology among participants in South Africa. This finding reflects differences in geographical location and lifestyle among the participants.…”
Section: Discussioncontrasting
confidence: 99%
“…In China, CIN 1 and CIN 2 pooled prevalence of 3.4% and 1.5% has been reported [ 42 ]. Contrary to our study, Ntuli et al [ 43 ] reported a higher proportion (19.2%) of abnormal cytology among participants in South Africa. This finding reflects differences in geographical location and lifestyle among the participants.…”
Section: Discussioncontrasting
confidence: 99%
“…The suboptimal uptake of cervical cancer screening identified in this study is a concern, especially for women living with HIV and considered at high risk of developing cervical cancer. This study reports an uptake that is lower than 46.4% and 65.4% in research conducted in Limpopo and Soweto, respectively [ 8 , 9 ]. Surprisingly, more women living with HIV in Limpopo Province, rural South Africa, were screened than women in this study, yet the latter was an urban area and part of the economic hub of South Africa.…”
Section: Discussionmentioning
confidence: 83%
“…For women living with HIV, the South African policy on cervical cancer recommends screening be done at three-year intervals starting as soon as HIV is diagnosed [ 6 ]. South African data showed that women living with HIV had a higher prevalence of HPV infection than women who were HIV-negative because of sexual behavior and immune suppression due to HIV infection [ 7 , 8 ]. Evidence reveals that the incidence and progression of the squamous intraepithelial lesion (SIL) and cervical cancer could be reduced by early ART initiation and adherence [ 9 - 13 ].…”
Section: Introductionmentioning
confidence: 99%